Age-stratified risk factors and predictive models for progression to lupus nephritis in patients with systemic lupus erythematosus: a review - Sun, Shuyu; Li, Song; Chang, Xin; Wu, Jian (Frontiers in Immunology, 2025)
Systemic lupus erythematosus (SLE) is a highly heterogeneous autoimmune disorder, and lupus nephritis (LN) is one of its most severe organ manifestations. The age at disease onset is a critical factor influencing the clinical phenotype, disease progression, and prognosis of SLE. However, few studies have specifically focused on the age-stratified risk of developing LN. This review examines the age-related clinical and immunological features of SLE and the risk factors associated with progression to LN. In addition, it systematically evaluates how current LN risk prediction models incorporate age as a variable. Although many existing models include age, a significant gap remains-no tools have been specifically designed to assess LN risk across different age groups. Therefore, developing age-specific LN risk prediction models and tailored management strategies is crucial to improving patient outcomes. Such approaches would enable the early identification of high-risk patients and facilitate individualized interventions, ultimately leading to improved long-term renal outcomes for patients with SLE.